On the Negative Relationship between Labor Income Uncertainty and Homeownership : Risk Aversion vs. Credit Constraints - Luis Diaz-Serrano (Institute for the Study of Labor (IZA), 2004)
Barriers to homeownership have traditionally been an important research and policy issue. In particular, the role of income volatility and credit constraints have been one of the main focuses in this concern. In this paper we test for the first time whether the underlying nature behind the negative effect of income uncertainty on the owner-occupancy propensities is driven by risk aversion, as it is assumed in most of the theoretical models, or on the contrary it is driven by credit constraints. The former question emerges from the plausible assumption that households facing higher income volatility are also expected to face borrowing constraints. To disentangle this puzzle, we use an unusually rich data coming from the Italian Survey of Household Income and Wealth carried out by the Bank of Italy. Our results confirm that in Italy both labor income uncertainty and credit constraints exert a significant negative effect on the probability of homeownership. Our main findings indicate that the negative relationship between labor income uncertainty and the owner-occupancy propensities are just driven by households? risk aversion, while credit constraints play no role.
Keywords: J0; R0; D1; 330; homeownership; income uncertainty; credit constraints; risk aversion; Wohneigentum; Lohn; Risiko; Verschuldungsrestriktion; Risikoaversion; Schätzung; Italien